Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
45 - (x - 9) = -35
45 + 35 = x - 9
=> x - 9 = 80
x = 80 + 9
x = 89
Vậy x = 89
Ủng hộ mk nha ^_^
a) 31 - ( 16 + 31 ) = x - ( 45 - 75 )
31 - 16 - 31 = x - 45 + 75
-16 = x + 30
x = -46
b) 9 - 45 = ( 8 - x ) - ( 35 + 8 )
-36 = 8 - x - 35 - 8
-36 = -x - 35
-x = -1
x = 1
a) (-37 - 17) . (-9) + 35 . (-9 - 11)
=-54*(-9)+35*(-20)
=486+(-700)
=-214
b) (-25) . (75 - 45) - 75 . ( 45 - 25)
=(-25)*30-75*20
=-750-1500
=-2250
-5x -(-3) = 13
-5x + 3 = 13
-5x = 13 - 3
-5x = 10
x = 10 : (-5)
x = -2
45 - (x - 9) = -35
45 - x + 9 = -35
45 - x = -35 - 9
45 - x =-44
x = 45 - (-44)
x = 89
15 - (x - 7) = -21
15 - x + 7 = -21
15 - x = -21 - 7
15 - x = -28
x = 15 - (-28)
x = 43
(-5) + x = 15
x = 15 - (-5)
x= 20
cau1 :120-(100+x)=25
100+x=120-25
100+x=95
x=-5
cau2: 5(x+23)+6=96
5(x+23)+6=96
5(x+23)=90
x+23=18
x=-5
cau3: 100-(25+x)=40
25+x=100-40
25+x=60
x=35
cau4: 35-9(x+2)=45
9(x+2)=-10
x+2=-10/9
x=-28/9
45-(x-9)=-35
=> x - 9 = 45 - ( -35 )
=> x - 9 = 80
=> x = 80 + 9
=> x = 89
Vậy x = 89
45-(x-9)=-35
x-9=45+35
x-9=80
x=80+9
x=89